Elucidation of Abiotic Stress Signaling in Plants 2015
DOI: 10.1007/978-1-4939-2211-6_13
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal, Triose Phosphate Isomerase, and Glyoxalase Pathway: Implications in Abiotic Stress and Signaling in Plants

Abstract: Methylglyoxal (MG) is a cytotoxic metabolite inevitably produced as a side product of primary metabolic pathways via both enzymatic and non-enzymatic reactions. In plants, spontaneous generation of MG through breakdown of triose sugars (dihydroxyacetone phosphate and glyceraldehyde 3-phosphate) is believed to be the major route for MG formation. MG is maintained at basal levels in plants under normal conditions that accumulate to higher concentrations under various stresses, probably as a general consequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 118 publications
1
11
0
Order By: Relevance
“…The 26S proteasome is known to degrade proteins including damaged proteins tagged with ubiquitin and also confers tolerance to various stresses (Kurepa et al 2009;Ueda et al 2011). Triose phosphate isomerase levels have been reported to increase under different stresses to prevent accumulation of cytotoxic metabolites (Kaur et al 2015). Triose phosphate isomerase is involved in glycolytic pathway, pentose phosphate pathway and carbon metabolism and distribution (Dorion et al 2012) and sugar metabolism (Ito et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The 26S proteasome is known to degrade proteins including damaged proteins tagged with ubiquitin and also confers tolerance to various stresses (Kurepa et al 2009;Ueda et al 2011). Triose phosphate isomerase levels have been reported to increase under different stresses to prevent accumulation of cytotoxic metabolites (Kaur et al 2015). Triose phosphate isomerase is involved in glycolytic pathway, pentose phosphate pathway and carbon metabolism and distribution (Dorion et al 2012) and sugar metabolism (Ito et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…leaves or roots), and the physiological state of the whole plant ( Kaur et al, 2015a , b ). Spontaneous production of MG occurs as a consequence of glycolysis, in metabolically active plant cells, from the reaction of the triose sugar phosphates glyceraldehyde-3-phosphate (G3P) and dihydroxyacetone phosphate (DHAP), both of which are photosynthetic intermediates ( Yadav et al, 2005a ; Takagi et al, 2014 ; Kaur et al, 2015a , b ). This reaction is considered to be the principal route for MG formation under normal physiological conditions ( Figure 1 ).…”
Section: Mg Synthesis In Plantsmentioning
confidence: 99%
“…The reactive alpha-ketoaldehyde MG is cytotoxic to plant cells at high cellular concentrations, but it may act as an important signaling molecule at low concentrations ( Yadav et al, 2005a , b ; Singla-Pareek et al, 2006 ; Hossain et al, 2009 ; Kaur et al, 2015a , b ). MG is produced in plant cells as a result of glycolysis, and its celluar concentrations are maintained at very low levels in the absence of any environmental stress ( Kaur et al, 2015b ). However, in response to abiotic stressors celluar concentrations of MG rapidly increase ( Yadav et al, 2005a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…The production of MG in response to various environmental cues and its subsequent detoxification by the glyoxalase pathway, together with its ability to trigger a widespread plant response, makes MG and glyoxalases suitable biomarkers for stress tolerance [15]. A large volume of evidence resulting from in vivo and in silico studies has revealed MG to be a central metabolite controlling signal transduction, gene expression and protein modification [16,17]. To date, several genome-wide analyses have been carried out that located the presence of multiple glyoxalase isoforms in all the plant species studied.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several genome-wide analyses have been carried out that located the presence of multiple glyoxalase isoforms in all the plant species studied. A total of 11 GLYI and 5 GLYII genes in Arabidopsis thaliana [18], 11 GLYI and 3 GLYII in Oryza sativa [18], 24 GLYI and 12 GLYII in Glycine max [19], 29 GLYI and 14 GLYII in Medicago truncatula [20] and, 16 GLYI and 15 GLYII in Brassica rapa [21] have been identified. Fig.…”
Section: Introductionmentioning
confidence: 99%